1994
DOI: 10.1086/187599
|View full text |Cite
|
Sign up to set email alerts
|

Deep imaging of the double quasar QSO 0957+561: New constraints on H[SUB]0[/SUB]

Abstract: In this Letter we present new results from extremely deep, high-resolution images of the eld around the double quasar QSO 0957+561. A possible gravitational arc system near the double quasar has recently been reported, which, if real, would set strong constraints on determinations of the Hubble constant from the time delay in the double quasar. We nd that both the morphology and the colors of the claimed arc systems suggest that they are chance alignments of three and two di erent objects, and not gravitationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…This was perhaps due to the lack of lensing candidates with lenses at different redshifts. However, recent observations of the lens systems 2345+007 (Pelló et al 1996), 2016+112 (Lawrence, Neugebauer, & Matthews 1993), and 0957+561 (Bernstein, Tyson, & Kochanek 1993; but see Dahle, Maddox, & Lilje 1994) suggest that these systems may involve lenses at different redshifts.…”
Section: Introductionmentioning
confidence: 96%
“…This was perhaps due to the lack of lensing candidates with lenses at different redshifts. However, recent observations of the lens systems 2345+007 (Pelló et al 1996), 2016+112 (Lawrence, Neugebauer, & Matthews 1993), and 0957+561 (Bernstein, Tyson, & Kochanek 1993; but see Dahle, Maddox, & Lilje 1994) suggest that these systems may involve lenses at different redshifts.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, large clusters of galaxies (which are both massive and centrally condensed) are especially good gravitational lens candidates, and detections of the coherent pattern of weak-lensing shear due to a number of clusters has led to interesting constraints on the masses of these objects (e.g., Tyson, Wenk, & Valdes 1990 ;Dahle, Maddox, & Lilje 1994 ;Fahlman et al 1994 ;Mellier et al 1994 ;Smail, Ellis, & Fitchett 1994 ;Smail et al , 1997Tyson & Fischer 1995 ;Smail & Dickinson 1995 ;Kneib et al 1996 ;Seitz et al 1996 ;Squires et al 1996aSquires et al , 1996bBower & Smail 1997 ;Luppino & Kaiser 1997 ;Clowe et al 1998 ;Hoekstra et al 1998). Although more controversial than the results for lensing clusters, detections of systematic weak lensing of distant Ðeld galaxies by foreground Ðeld galaxies have been reported, and these have been used to place constraints on the physical sizes and total masses of the dark matter halos of the lens galaxies (e.g., Brainerd, Blandford, & Smail 1996 ;Griffiths et al 1996 ;Ebbels 1998 ;Hudson et al 1998 ;Natarajan et al 1998 ;DellÏAntonio & Tyson 1996 ;Fischer et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Zuo et al (1997) found a differential reddening in spectrum A as compared to spectrum B and deduce a dust to gas ratio of $0.6 in the DLA. Imaging of the quasar field has been reported by Dalhe, Maddox, & Lilje (1994;ground based) and Bernstein et al (1997;WFPC2/Hubble Space Telescope [HST ]). Despite these efforts, the luminous object associated with the z ¼ 1:3911 absorber remains unidentified.…”
Section: Introductionmentioning
confidence: 99%